Exploring previous studies related to the development of pupils with special education needs visual impairment through the planning of individual education plans - Nordin, Mohd Norazmi; Ahad, Rosnee; Rosdi, Bella; Magiman, Mohamad Maulana; Abbas, Mohd Saleh; Mosbiran, Nor Fauziyana (Auricle Global Society of Education and Research, 2024)
The development of MBPK is a change that occurs to MBPK after undergoing several phases in their learning. Their development can be seen in terms of academics, sports, personality and co-curricular. In making the wish to see MBPK develop well, all parties need to play a role in its implementation. MBPK develops gradually and depends on the intervention that is the stimulus for the development. The development of MBPK can happen well if teachers can prepare learning sessions effectively. Student language development can be developed with the help of the teacher's skills in planning and implementing lessons. This qualitative study uses observation, interview and document analysis methods as a means of obtaining data. The findings of the study show that the learning process for nonverbal skills can be carried out more effectively if the teacher can master the knowledge related to speech therapy. As a suggestion, they hope that innovation can be done in the learning process, as well as parents, Special Education teachers and Pupil Management Assistants need to be given knowledge through training and workshops.